Justice, democracy and the siting of nuclear waste repositories: the Buan and Gyungju cases of South Korea - Huh, Youngsoo, author; MacDonald, Bradley J., advisor; Duffy, Robert J., committee member; Mumme, Stephen, committee member; Kim, Joon, committee member (Colorado State University. Libraries, 2013)
Siting a radioactive waste repository in a nation is one of the most controversial environmental issues to date. During the last two decades, the Korean government has failed to site a repository in the face of vehement opposition from the potential host sites. The repeated failures of the Korean government's siting policy are due to the fact that it relied on the DAD (Decide, Announce and Defend) siting policy emphasizing the technical and economic criteria while neglecting the demands from the local communities to participate in the decision making process. As a consequence, the Korean government discarded the conventional DAD policy to adopt the VA (Voluntary Approach), which is based on participatory democracy. In 2005, this change in the siting policy took effect resulting in the competitive referenda to host the repository in four cities, in which Gyungju City won the competition. Three requirements for the VA siting policy are safety, compensation and the democratic procedure. No doubt that safety and compensation are the minimum requirements for any siting policy. However, the Korean cases prove that the democratic procedure is a more crucial factor over safety and compensation in order to obtain the local community's acceptance of the facility. The most basic assumption of the VA is that the host communities should not be sacrificed to serve the interests of the rest of the country. Therefore, the siting is feasible only when it can benefit both the host communities and the rest of the country together. In this respect, the democratic procedure in the VA must include the concepts of justice, which takes into account the long-term effects of the siting on the host communities. Hence, the Korean cases will be analyzed in terms of whether the ideal conceptions of justice and democracy are practiced in the siting process. In particular, the "Buan Conflict" and the "Gyungju Referendum" will be compared and analyzed in detail since they represent the two typical examples of success and failure in the Korean siting policy. The process leading to the resolution at Gyungju, however, is too flawed to be considered democratic. Also from the perspective of environmental justice, the Gyungju siting has many problems. Nevertheless, even the imperfect democracy practiced in Gyungju achieved significant success since it contained the most essential element of the VA: self-determination by the affected people. Despite its limitation, the Gyungju case illustrates how the VA has the best potential to elicit a social consensus required to solve the nuclear waste siting dilemma.
Keywords: Buan and Gyungju; compensation and safety; democratic procedure; Korean siting strategy; nuclear waste repository; voluntary approach